Franchises in the frame of the new economy (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2009)
The managerial current thought realizes that the organizations constantly face a changeable and complex reality. It motivates flexibility of its structures, that develop the possibility of facing the changes that are generated so much inside and out of it, this also have to be capable of adapting permanently its processes the demands that the public demands, not only for the production of goods and the rendering of services but the requirements that the community generates where the activities are carried out, among others. The organizations must be highly adaptative, and this investigation shows how high they are when the technological changes face the new economy, business, telecommunications, infrastructures, and the society of the information and the communication. That is the reason why the sector of exemptions franchises of snack food of international nature in the item of hamburgers in Barquisimeto was selected as object of study. Then it was applied the protocol sandardized of Cisco Systems, company specializing in the technology of the information and communication; determining the preparation of the sector to incorporate the technological solutions in the development of the marketing of their products and services in the digital economy. The conclusions appear depending on the contradictions, paradoxes, utopias, challenges and challenges of the sector as for the preparation that was revealing the results of Cisco Systems
Keywords: technological innovations; digital economy; standardized protocol cisco systems